Gelatin Extraction and Characterization from Femur Bones of Bovine and Porcine with Acid Process - Purwantiningsih Sugita; Muhamad Rifai; Ambarsari, Laksmi; Rahayu, Dyah Utami Cahyaning; Dianhar, Hanhan (Tropical Biopharmaca Research Center, IPB University, 2021)
Gelatin has been widely used as an additive in food industry pharmaceutical, and cosmetic. The similar physical appearance between bovine and porcine gelatin causes an issue for some communities like a Muslim due to awareness of halal food. This study aims to produce gelatin from femur bones of bovines with acid hydrolysis and their characteristics compared to standard gelatin of bovine and porcine. Bovine and porcine bones were soaked in 5% HCl for 10 days and every 2 days a HCl solution was replaced to get ossein. Ossein is hydrolyzed by gradual heating at 65, 75, and 85oC. Gelatin confirmed by the physico-chemical characters, FT-IR and analysis amino acid with HPLC.The results showed that the yield of bovine gelatin was 4.33%. The physico-chemical characters of bovine gelatin resulting from isolation and bovine gelatin standards are in conformity with porcine gelatin standards and meet the requirements of SNI 06-3735-1995 and GMIA. Therefore, bovine gelatin is specifically capable of substituting porcine gelatin for application in the pharmaceutical field. The FTIR spectrum of bovine gelatin shows the presence of amide A, amide I, amide II and amide III groups. The amino acid characters of gelatin were identified as glycine (13.57%) and proline (1.62%) for bovine gelatin and glycine (0.51%) and proline (0.09%) for porcine gelatin.